Causes of Technological Gap in Green Gram Cultivation in District Ramabai Nagar U.P. (Indian Journal of Extension Education, 2019)
The study was carried out in district Ramabai Nagar of U.P. Two Blocks selected, four villages, two form each development blocks and 80 respondents were selected for the study. Most of the respondents belonged of the middle age group, 56.25 per cent respondents belonged to backward caste. The analysis of technology gap in green gram crop showed that highest gap was found about knowing the insect, pest disease and their control and the lowest gap was found about knowing of the sowing time. The findings revealed that wider technological gaps exist in the farmers about the production recommendation for green gram cultivation. This gap in most of the green gram growing operations needs to be reduced, if the green gram yields have to improve on the famers’ field. Emphasis on green gram demonstration and farmer training for reducing the gaps is need of the hour.